Stenkast - Henningsen, Gustav; Laursen, Jesper (Kuml, 2006)
Cairns In Denmark, the term stenkast (a ‘stone throw’) is used for cairns – stone heaps that have accumulated in places where it was the tradition to throw a stone. A kast (a ‘throw’) would actually be a more correct term, as sometimes the heaps consist of sticks, branches, heather, or peat, rather than stones – in short, whichever was at hand at that particular place. A kast could also consist of both sticks and stones. The majority of the known Danish cairns were presented by August F. Schmidt in 1929. Since then, numerous new ones have been discovered, and we now know of around 80 cairns, cf. the list on page 264 and map Fig. 3. It appears from the descriptions that the majority – a total of 65 – are actual cairns, 14 are heaps of branches, whereas two are described as either peat or heather heaps. Geographically, the majority – a total of 53 – are found in Jutland, with most in North and Central Jutland (Fig. 3). Fifteen are known from Zealand, four from Lolland, four from Funen, and five from Bornholm. Topographically, they are found – naturally – where people would normally be passing: next to roads and in connection with sacred springs, chapels, and places of execution. However, they also occur in less busy places, in woods, along the coast, on moors, and on small islands. A few cairns have been preserved because they are still “active” as reminiscences of customs and habits of past times. This is the case of the cairn called Røsen (“røse” being another Danish term for a cairn) on Trøstrup Moor (no. 45, Fig. 1-2), of Heksens Grav (“The Witch’s Grave”) (no. 27, Fig. 4), and of the branch heap in the wood of Slotved Skov (no. 14, Fig. 5), which was recently revived after having been almost forgotten. Other cairns are maintained as prehistoric relics, as is the case of the branch heap by the name of Stikhoben (“The Stick Heap;” no. 10, Fig. 6) and Kjelds Grav (“Kjeld’s Grave,” no. 59, Fig. 7). Although heaps of stones and branches are included in the Danish Protection of Nature Act as relics of the past worthy of protection, so far merely the two latter have been listed. Whereas the remaining ’throws’ of organic material have probably disintegrated, it is still possible under favourable conditions to retrieve those made from more enduring materials – unless they have been demolished – even if they have practically sunk into oblivion (Figs. 8-10). The oldest known cairn is almost 500 years old. It was situated by the ford Præstbjerg Vad in Vinding parish near the Holstebro-Ribe highroad. Tradition says that the stone heap came into existence as a memorial of a priest in Hanbjerg, who died in the first half of the 16th century following a fall with his horse. Such legends of origin are connected with most of the Danish cairns. They usually tell of some unhappy or alarming happening supposed to have occurred at the place in question. However, they are often so vague and stereotype that they can only rarely be dated or put into a historical context. Indeed, on closer examination several of them turn out to be travelling legends. Apart from the legend of the murdered tradesman, they comprise the legend of the exorcised farmhand and that of the three sisters, who were murdered by three robbers, who turned out to be their own brothers. The latter legend, which is also known from a folksong, is connected to the so-called Varper on the high moor in Pedersker parish on Bornholm (no. 7). Until the early 20th century, it was the custom to maintain these cairns by putting back stones that had fallen down and adorn them with green sprigs. Early folklorists interpreted this as a tradition going back to an old sacrificial ritual, although the custom also seems to have had a pure practical purpose, as these stone heaps were originally cairns marking the road across inland Bornholm. A special group of the Danish cairns are connected with the tradition that someone is buried underneath them, such as a body washed ashore, a murdered child from a clandestine childbirth, a murdered person, several persons killed in a fight, an exorcised farmhand, a suicide, a murderer buried on his scene of crime, or witches and murderers buried at the place of execution. In all these cases, the throwing of a stone was supposed to protect the passers-by against the dead, who was buried in unconsecrated grounds and thus, according to public belief, haunted the spot. Another far less frequent explanation was that the stone was thrown in order to achieve a good journey or luck at the market. In some places, the traveller would throw the stone while shouting a naughty word or in other ways showing his disgust with the dead witch, criminal, or infanticide buried in that particular place. In rather a lot of the cases, as explained by the context, the cairn was merely a memorial to some unhappy occurrence, and the stone was thrown in memory of the deceased. In an article on Norwegian cairns written by the folklorist Svale Solheim, the author attached importance to achieving a clear picture of the position of the cairns (kastrøysarne) in the landscape. A closer examination showed that almost all were situated by the side of old roads – between farms and settlements, through forests, or across mountains – in short, where people would often walk. “The cairns follow the road as the shadow follows the man,” Solheim writes and gives an example of an old road, which had been relocated, and where the cairns had been moved to the new road. Furthermore, the position of the cairns along the roads turned out to not be accidental; they were always found at places that were in one way or other interesting to the travellers. This is why Solheim thought that the stone heaps mostly had the character of cairns or road stones thrown together at certain places for a pure practical purpose. “For instance,” he writes, “we find stone heaps at places along the roads where there is access to fine drinking water. These would also be natural places for a rest, and numerous stone heaps are situated by old resting places. And so it came natural to mark these places by piling up a stone heap, and of course it would be in every traveller’s interest to maintain the heaps.” The older folklore saw the tradition as a relic of pagan rituals and conceptions. As a reaction to this, Solheim and others took a tradition-functionalistic view, according to which most folklore, as seen in the light of the cultural conditions, was considered rational and the rest could be explained as pseudo beliefs, for instance educational fiction and tomfoolery. However, if we turn to our other neighbouring country, Sweden, it becomes more difficult to explain away that we are dealing with sacrificial rites, as here, the most used dialectal term for the stone and branch piles were offerhög, offervål, or offerbål (“offer” is the Swedish word for sacrifice), and when someone threw stones, sticks, or money on the pile, it was called “sacrificing.” An article from 1929 by the anthropologist Sigurd Erixon is especially interesting. Here, he documents how – apart from the cairns with a death motive (largely corresponding to the Danish cases mentioned above), Sweden had both good luck and misfortune averting sacrificial stone throwing (Fig. 13). Whereas the sacrificial cairns connected to deaths were evenly distributed across the whole country, Erixon found that the “good luck cairns” occurred mainly in environments associated with mountain pasture farming or fishing. Based on this observation and desultory comparative studies, Erixon formed the hypothesis that the “good luck cairns” represented an older and more primitive culture than the cairns associated with sacrifices to the dead. “The first,” he writes, “belong rather more to the work area of hunting, fishing, and animal husbandry, roads, and environments, whereas the death sacrificial cairns seem to be closer related to the culture of agriculture.” The problem with the folkloristic material is that most of it is based on reminiscences. In order to study the living tradition, one must turn elsewhere. However, as demonstrated by James Frazer in “The Golden Bough,” this is no problem, as the custom of throwing stones in a pile is known from all over the world, from Africa, Europe, and Asia to Australia and America (Fig. 14). Customs last, their meanings perish – the explanation why, for instance, one must throw a stone onto a stone pile, may be forgotten, or reinterpreted, or get a completely new explanation. The custom probably goes back further than any known religion. However, these have all tried to tally the stone throwing with their “theology.” In Ancient Greece, the stone piles by the roadsides were furnished with statues of Hermes (in the shape of a post with a head and sometimes a phallus). As an escort for the dead, Hermes became the god of the travellers, and just as the gods had thrown stones after Hermes when he was accused of murdering Argus, people could now do the same. With the introduction of Christianity, the throwing of stones was denounced as superstition, and a standard question for the penitents in the so-called books of penance was: “Have you carried stones to a heap?” All across Europe, crosses were planted in the stone heaps – which must have caused problems as it was considered a deadly sin to throw stones after a cross. In the culture connected with pilgrimage, the cairns got a new meaning as markers of important places. For instance, enormous stone piles outside Santiago de Compostela mark the location where pilgrims first spotted the towers of the city’s cathedral (Fig. 15). At many places, the cairns were consecrated to saints, so that now people would carry stones to them as a sacrifice or a penance. The jews also adopted the custom. The Old Testament mentions stone heaps gathered over murdered persons or placed around a larger stone, as the “witness dolmen” built by Jacob and his people to commemmorate his pact with Laban, his father-in-law. However, there is no mention of throwing new stones onto these heaps. However, the latter occurs in the still practiced Jewish custom of placing stones on the gravestones when Jews visit the graves of their dead (Fig. 16). Stone throwing in a Muslim context is illustrated by Edward Westermarck’s large investigation of rituals and popular belief with the Berbers and the Arabs in Marocco in the early 20th century. Unfortunately, it only comprises cairns connected to Muslim saints, but even with this limitation, the investigation gives an idea of the variety of applications. If the stone heap is situated near the grave of a saint, it may mark the demarcation of the sacred area, or it may have come into existence because the wayfaring have a habit of throwing a stone when they pass the grave of a saint, which they do not have time to visit. If the heap is situated on a ridge, it is usually an indication of the spot on a certain pilgrim route where the sacred places become visible for the first time. Other stone heaps mark the places where a holy man or woman is supposed to have been buried, or rested, or camped some time. By a large crossroads outside Andira, Westermark was shown a stone heap, which indicated that this place was the gathering place for saints, who met there at nighttime. The sacred cairns in Marocco are often easily recognized by the fact that they are chalked white at intervals. At some places, the cairns may also be marked with a pole with a white flag symbolising the sacred character of the place. Even Buddhism struggled against the stone heaps, especially in the form of the oboo cult, which was repeatedly reformered and reinterpreted by Buddhist missionaries. And in early 17th-century South America, the converted aristocratic Inca, Felipe Guaman Poma de Ayala, made sarcastic remarks about Indians, who “even now” had preserved the bad habit of [sacrificing to] stone heaps (apachitas).” Historically, the Danish cairns can be documented from the 16th century, but the tradition may well be older. Seen in a larger, comparative context, heaps of stones and branches represent an ancient tradition rooted in the deepest cultural layers of mankind. Thus, as cultural relics, they are certainly worthy of preservation, and we ought to put a lot of effort into preserving the few still existing. Whereas it will probably be difficult to establish possible prehistoric stone heaps using archaeology, the possibilities of documenting hitherto unknown stone piles from historical times is considerably higher, if special topographic conditions are taken into consideration. In connection with small mounds on tidal meadows or stone heaps along stretches of old roads and by fords, old places of execution, springs, and grave mounds used secondarily for gallows, one should pay attention to such structures, which may well prove to be covering a grave. In a folklore context, the Danish stone heaps must be characterized as mainly “death sacrifice throws,” whereas only few were “good luck throws.” Due to the limited size of the country, and early farming, cairns and other road marks have not played the same role as a help for travellers and traffic as it did in our neighbouring countries with their huge waste areas. If the stone piles are considered part of a thousands of years old chain of traditions, they belong to the oldest human “monuments.” The global distribution of the phenomenon endows it with a mystery, which, during a travel in Mongolia, Haslund-Christensen caught with a stroke of genius: “We stood before an oboo, one of the largest I have ever seen...one of those mysterious places of sacrifice which are still secretly preserved, built of stone cast upon stone through many generations; a home of mystery which has its roots in the origin of the people itself, and whose religious significance goes much further back in time than any of the religions in the modern world.” Gustav Henningsen Dansk Folkemindesamling Jesper Laursen Moesgård Museum Translated by Annette Lerche Trolle